1999
DOI: 10.1002/(sici)1521-4109(199907)11:9<660::aid-elan660>3.0.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Redox Kinetics Measurements of Probucole Using Square-Wave Voltammetry

Abstract: Probucole is both electroactive and a surface-active compound. It undergoes fast and chemically reversible reduction at a HMD electrode in either 0.1 mol dm À3 KClO 4 or 1 mol dm À3 KNO 3 . Both probucole and its electrode reduction product are strongly adsorbed to the electrode surface and the overall electrode mechanism exhibits characteristic properties of a surface redox reaction. The kinetics of the surface redox reaction of probucole is measured by means of square-wave voltammetry. The kinetic parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…The quasireversible maximum for these types of electrode reactions emerges from the specific chronoamperometric properties due to immobilization of the reactant and the current sampling procedure of square-wave voltammetry. The quasireversible maximum was studied thoroughly in the case of surface electrode reactions and widely exploited for estimation of charge transfer kinetics [33,35]. In the present mechanism, the quasireversible maximum is associated with the thin films, when the film is significantly exhausted during the potential scan enabling a repetitive turnover of the electroactive material.…”
Section: Quasireversible Electrode Reactionmentioning
confidence: 99%
“…The quasireversible maximum for these types of electrode reactions emerges from the specific chronoamperometric properties due to immobilization of the reactant and the current sampling procedure of square-wave voltammetry. The quasireversible maximum was studied thoroughly in the case of surface electrode reactions and widely exploited for estimation of charge transfer kinetics [33,35]. In the present mechanism, the quasireversible maximum is associated with the thin films, when the film is significantly exhausted during the potential scan enabling a repetitive turnover of the electroactive material.…”
Section: Quasireversible Electrode Reactionmentioning
confidence: 99%
“…Over the last decade, significant efforts have been undertaken in modeling and simulations of the surface electrode processes, revealing that SWV is particularly appealing for mechanistic, kinetic, and thermodynamic characterization of surface electrode processes, including proteins and enzymes [27,[46][47][48][49][50][51][52][53][54][55]. So far, a plethora of electrode mechanisms have been considered, including simple surface electrode reactions [46,47,[56][57][58][59][60][61], surface reactions with uniform interactions [62], surface electrode reactions coupled with a preceding [63] or following chemical reaction [64], surface catalytic mechanisms [65,66], twostep surface reactions [67,68], and two-step reactions coupled with an intermediate chemical step (ECE -or electrochemical-chemical-electrochemical reaction scheme) [69]. The list of surface mechanisms can be easily extended, as the mathematical modeling of surface processes, although not easy, is yet simpler than in the case of common diffusion controlled processes.…”
Section: Representative Examples Of Enzymes Studied With Protein Filmmentioning
confidence: 99%
“…The adsorptive stripping voltammetric behaviour of various V(V) complexes is well documented in the literature [4][5][6][7][8][9][10][11][12]. A large number of adsorptive stripping voltammetric methods have been reported for determination of vanadium in a form complex created with solochrome violet RS [4], catechol [5,6], 2,5-dichloro-l,4-dihydroxy-3,6-benzoquinone (chloroanilic acid) [7], 2-(5-thiozalolylazo)-p-cresol [8], pyrogallol [9], 8-hydroxyquinoline [10], antipyrylazo III [11] and cupferron [12]. In this paper we demonstrated that the redox reaction of V(V) in ammonia buffer of pH = 8.6 exhibits properties of a surface redox reaction.…”
Section: Introductionmentioning
confidence: 99%